2020
DOI: 10.1523/eneuro.0209-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Single-Pulse TMS over the Parietal Cortex Does Not Impair Sensorimotor Perturbation-Induced Changes in Motor Commands

Abstract: Intermittent exposure to a sensorimotor perturbation, such as a visuomotor rotation, is known to cause a directional bias on the subsequent movement that opposes the previously experienced perturbation. To date, it is unclear whether the parietal cortex is causally involved in this postperturbation movement bias. In a recent electroencephalogram study, Savoie et al. (2018) observed increased parietal activity in response to an intermittent visuomotor perturbation, raising the possibility that the parietal cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 86 publications
(124 reference statements)
1
8
0
1
Order By: Relevance
“…Regarding early involvement, evidence for modulation of early ERP components within the first 200ms is generally considered weak (see systematic review in (Nieuwland, 2019)), because such early effects are typically small or highly variable across studies as they tend to strongly vary with task and stimulus (Pulvermuller et al, 2009). For instance, an early involvement of the right AG at 140ms during a visuomotor adaptation task (Savoie et al, 2018) was not replicated in a follow-up experiment that used a single-pulse TMS delivered at around 150ms over the same region (Savoie et al, 2020). Nevertheless, such early effects might reflect the exertion of different rapid parallel processes (Strijkers et al, 2017).…”
Section: Discussion Of Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding early involvement, evidence for modulation of early ERP components within the first 200ms is generally considered weak (see systematic review in (Nieuwland, 2019)), because such early effects are typically small or highly variable across studies as they tend to strongly vary with task and stimulus (Pulvermuller et al, 2009). For instance, an early involvement of the right AG at 140ms during a visuomotor adaptation task (Savoie et al, 2018) was not replicated in a follow-up experiment that used a single-pulse TMS delivered at around 150ms over the same region (Savoie et al, 2020). Nevertheless, such early effects might reflect the exertion of different rapid parallel processes (Strijkers et al, 2017).…”
Section: Discussion Of Sectionmentioning
confidence: 99%
“…There are obviously many EEG/MEG and TMS/TES studies that did not find any significant effects in the AG when such effects were hypothesized or predicted a priori. For example, no significant role for the AG was identified for semantic memory Chao, 2001), verb-argument combinations (Kim and, color and form binding (Esterman et al, 2007), lexical integration (Lopopolo et al, 2021), idiomatic processing (Boulenger et al, 2012), semantic integration of gesture and speech (He et al, 2018b), thematic processing (Teige et al, 2019), semantic processing at the level of N400 (Kielar et al, 2015), syntactic manipulation (Matar et al, 2021), combinatorial processing (Pylkkanen et al, 2014), associative memory encoding (Koen et al, 2018), visual tactile multisensory integration (Pasalar et al, 2010), and in adaptive behaviour in post-perturbation movement bias (Savoie et al, 2020).…”
Section: Bias Toward Positive Ag Effectsmentioning
confidence: 99%
“…First of all, Desmurget himself showed that one of his participants, who had been stimulated more medially than the others, showed a slightly different pattern of results (Desmurget et al 1999 ). In addition, subsequent studies did not observe any suppression of movement adjustments even if they stimulated the same area as in Desmurget’s study (Johnson and Haggard 2005 ; Savoie et al 2020 ). Lastly, another TMS study targeting more medial/anterior parts of the PPC did not show any effect of the stimulation (Marigold et al 2019 ).…”
Section: Introductionmentioning
confidence: 68%
“…rTMS generally functions in the dorsolateral PFC (DLPFC) ( Lefaucheur et al, 2020 ). Single-pulse TMS uses frequent sites of action, such as the primary motor cortex (M1) ( Savoie et al, 2020 ). tDCS and tACS cathode and anode positions: contralateral orbit (SO), primary sensory cortex (S1) ( Marlow et al, 2013 ; May et al, 2021 ).…”
Section: Non-invasive Brain Stimulationmentioning
confidence: 99%